Kekuatan Bundling Mainan dalam Meningkatkan Penjualan Makanan Cepat Saji - Aulia Rahmawati; Yulda Aditya; Hikmal Fahri Ramadhan; Risky Putra Asikin; Bachri Cahyo Baskoro (Fakultas Ekonomi Dan Bisnis, Universitas Pembangunan Nasional Veteran Jakarta, 2025)
This study aims to explore the effect of the bundling strategy in the form of toys in McDonald's “Happy Meal” packages on sales levels and customer satisfaction. The research used a quantitative approach through a questionnaire distributed to 50 respondents of various ages. The aspects studied include health, customer loyalty, psychological influence, and pricing. The results showed that the bundling strategy was effective in increasing purchase intention and customer satisfaction, especially through the appeal of toys targeted at children and parents. However, there were still some concerns regarding the nutritional value of the products, which could be improved by adding healthy food options. This successful bundling strategy shows the potential to expand market share and increase revenue, while maintaining a balance between price, added value, and consumer preferences Keywords: Happy Meal, consumer preferences, customer satisfaction Abstrak Penelitian ini bertujuan untuk mengeksplorasi pengaruh strategi bundling berupa mainan dalam paket